2004
DOI: 10.1076/ocii.12.1.45.28067
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between allergen-specific IgE serum levels in patients with allergic conjunctivitis in spring

Abstract: These results suggest that cypress pollen was the largest cause of allergic conjunctivitis and that the total IgE level had no correlation with each specific IgE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 2 publications
1
27
0
Order By: Relevance
“…A prevalent idea is that hypersensitivity responses to external allergens such as pollen and house dust are the main causative factors in the development of allergic diseases. 1,2 However, little attention has been given to the internal factors such as the biometrical structure of the eye. This paper introduces the novel concept that refractive error could be responsible for allergic conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…A prevalent idea is that hypersensitivity responses to external allergens such as pollen and house dust are the main causative factors in the development of allergic diseases. 1,2 However, little attention has been given to the internal factors such as the biometrical structure of the eye. This paper introduces the novel concept that refractive error could be responsible for allergic conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…Cedar and cypress pollen have been identified as the major allergen sources of allergic conjunctivitis in spring. 4 However, little is known about causative allergens of allergic conjunctivitis in autumn.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that the highest positivity rate for a specific allergen was 52.5% for cedar pollen, followed by cypress pollen at 37.5% in spring [1]. Cedar pollen has been identified as the major allergen that causes allergic conjunctivitis in spring [1,14]. However, no studies have investigated specific IgE levels in tear fluid of patients with allergic conjunctivitis during autumn.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, allergic conjunctivitis shows two peaks, which are in spring and in autumn. Our previous study demonstrated that the highest positivity rate for a specific allergen was 52.5% for cedar pollen, followed by cypress pollen at 37.5% in spring [1]. Cedar pollen has been identified as the major allergen that causes allergic conjunctivitis in spring [1,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation